"Gifts and Calling": The Fruits of Coming to Know Living Jews - Langer, Ruth (Studies in Christian-Jewish relations, 2017)
In the process of implementing Nostra Aetate's teachings about Jews and Judaism, the Catholic Church came to realize that its leaders and laity needed to come to know Jews. This process has deeply transformed Catholic-Jewish relations, as is evident in the Vatican's Commission for Religious Relations with the Jews newest document The Gifts and Calling of God are Irrevocable' (Rom 11:29): A Reflection on Theological Questions Pertaining to Catholic-Jewish Relations on the Occasion of the 50th Anniversary of Nostra Aetate (No. 4). This essay will first trace the emergence of this living engagement and then turn to an analysis of how it has shaped this new document.